Overview of Tuberculosis Epidemiology at PKU Muhammadiyah Bantul Hospital in 2021-2023 - Sukirto, Novi; Yuniasih, Dewi; Prisilla, Elvina; Umam Kurniawan, Nurcholid; Budi Rahayu, Ana; Awisarita, Wiwara; Ariani, Rizka (Ahmad Dahlan Medical Journal, 2024)
The number of tuberculosis cases reported in Bantul Regency in 2022 was 732 cases. Aims this study to determine the epidemiological picture of tuberculosis in PKU Muhammadiyah Bantul Hospital in 2023. Research method: The research method applied in this study was the analytical observational method. The design in this study was cross-sectional. Tuberculosis cases at PKU Muhammadiyah Bantul Hospital in 2021-2023 experienced fluctuations and based on gender, the most cases were 54% males, the most tuberculosis patients were in the age group of 55-64 years, 86% of patients resided in Bantul Regency, the classification of tuberculosis was more in pulmonary tuberculosis, namely 72%, based on the results of the thoracic examination, 68% were known to be positive for tuberculosis, 17% of tuberculosis patients were accompanied by diabetes mellitus and 2% of tuberculosis patients were confirmed HIV positive. The conclusion is Patients at PKU Muhammadiyah Bantul Hospital were more male than female. Most of the patients in the age group of 55-64 years, and resided in Bantul. The TB diagnosis is most pulmonary tuberculosis, with more positive thoracic examination results, fewer patients with diabetes mellitus, and fewer HIV-positive tuberculosis patients. Keywords: epidemiology, characteristics, tuberculosis